CAREER PREFERENCE ASSESSMENT OF AGRICULTURAL STUDENTS USING PAIRED COMPARISION METHOD - MRIDULA N* and SAKEER HUSAIN A, (The Journal of Research ANGRAU, 2020)
The study was conducted among 300 agricultural graduates of Kerala state to find their most preferredjob among the five options selected by the judges, viz., Assistant Professor, Agricultural Officer, Banker,Farmer and Agripreneur. Paired comparision method, established by L.L. Thurston, based on the law ofcomparative judgement was used for the study. From the scale values obtained it was found that the mostpreferred job was that of an agricultural officer and least preferred job was of that of a farmer. The reluctance ofagricultural students to take up farming and agripreneurship calls for attention to the fact that they should begiven proper orientation regarding the emerging opportunities in these arenas during their undergraduate educationperiods. This is essential to channelize the skilled and knowledgeable manpower into the farming and agribusinesssector and to contribute to the sustainable entrepreneurship scenario of this agricultural country.